How convergent are rice export prices in the international market - Valera, Harold Glenn A.; Holmes, Mark J.; Pede, Valerien O.; Balié, Jean (Wiley, 2023)
This study revisits the issue of long‐term price convergence of rice export prices for India, Pakistan, Thailand, Uruguay, the United States, and Vietnam using a two‐stage pairwise unit root testing approach. To deduce evidence or lack of proof of convergence in price series, we also examine convergence using sigma and beta convergence specified in both unconditional and conditional frameworks. The methodology used is driven by the need to address three key concerns: (i) the likelihood of finding stationary price differentials, (ii) the magnitude of these differentials, and (iii) their speed of adjustment. To evaluate these concerns, we use monthly data for 18 price series drawn from these six countries from September 2011 to February 2021. The evidence points to a lack of international convergence. This gives rise to the possibility that a shield from a general downward export price trend is already in place for some exporters. Furthermore, we find that the likelihood of convergence is greater between pairs of price series that are characterized as high quality or having the same country of origin or having similar market share. Evidence also suggests that a converged pairing is more likely to have a smaller price differential if both price series are for low‐quality rice.